The quranic philosophy on superiority of audio sense against visual sense based on the book of exegesis and science reports - Sempo M.W.; Salam R.A.; Mohd R.A.; Zainudin W.N.R.A.B.; Zainol Z.B.; Zaki Z.B.M.; Ibrahim M.A.B.; Sayuti M.N.S.M. (American Scientific Publishers, 2024)
Index by Scopus